2011
DOI: 10.1002/cyto.a.21061
|View full text |Cite
|
Sign up to set email alerts
|

Cytometric assessment of mitochondria using fluorescent probes

Abstract: Mitochondria are most important organelles in the survival of eukaryotic aerobic cells because they are the primary producers of ATP, regulators of ion homeostasis or redox state, and producers of free radicals. The key role of mitochondria in the generation of primordial ATP for the survival and proliferation of eukaryotic cells has been proven by extensive biochemical studies. In this context, it is crucial to understand the complexity of the mitochondrial compartment and its functionality and to develop exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
249
1
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(268 citation statements)
references
References 124 publications
(164 reference statements)
9
249
1
9
Order By: Relevance
“…This hypothesis is supported by the fact that the number of TLT cells with depolarized mitochondria was increased after exposure to As 2 O 3 . It is important to note that changes in oxygen consumption can occur a long time before changes in membrane potential become measurable (26). Overall, these observations indicate that As 2 O 3 could act on the mitochondrial respiratory chain by enhancing intracellular ROS production mediated by decreased GSH levels.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This hypothesis is supported by the fact that the number of TLT cells with depolarized mitochondria was increased after exposure to As 2 O 3 . It is important to note that changes in oxygen consumption can occur a long time before changes in membrane potential become measurable (26). Overall, these observations indicate that As 2 O 3 could act on the mitochondrial respiratory chain by enhancing intracellular ROS production mediated by decreased GSH levels.…”
Section: Discussionmentioning
confidence: 77%
“…When dispersed in this manner JC-1 fluoresces green. Consequently, mitochondrial depolarization is indicated by a decrease in the red-green fluorescence intensity ratio (26). Data acquisition was done using a FACSCalibur flow cytometer (Becton Dickinson), and data were analyzed with FlowJo software (Tree Star, Inc.).…”
Section: Measurement Of Mitochondrial Membrane Potentialmentioning
confidence: 99%
“…To assay the metabolic capacity of tumor-infiltrating T cells, we measured mitochondrial function and mass by flow cytometry using MitoTracker Deep Red FM (a membrane permeable, carbocyanine-based dye for mitochondria used previously to stain mitochondrial mass; Cottet-Rousselle et al, 2011) and competency for glucose uptake using fluorescent 2-NBD-glucose (2NBDG) in T cells infiltrating implantable tumors. While Mito-Tracker Deep Red has been shown to be membrane potential sensitive in some systems, uncoupling using carbonyl cyanide m-chlorophenyl hydrazine (CCCP) showed that, using our staining protocols, MitoTracker Deep Red was highly resistant to collapse of membrane potential, especially compared to tetra-methylrhodamine ester (TMRE), a well-known membranepotential sensitive dye ( Figure S1A).…”
Section: Tumor-infiltrating T Cells Display Decreased Mitochondrial Massmentioning
confidence: 99%
“…and MitoSOX red (MSR, Thermo Fisher Scientific Co.) were used as fluorescent probes for mitochondrial membrane potential and for mitochondria-derived ROS, respectively [28]. …”
Section: Measurements Of Mitochondrial Membrane Potential and Mitochomentioning
confidence: 99%